Fam172a Mediates the Stimulation of Hypothalamic Oxytocin Neurons to Suppress Obesity‐Induced Anxiety - Baocheng Wan; Lina Zhang; Xinyu Wang; Rong Zhang; Lianxi Li; Yi Zhang; Zhuo Chen; Cheng Hu (Advanced Science)
Abstract Anxiety disorder is the most common mental disorder worldwide. Although human studies have demonstrated a positive association between obesity and anxiety disorder, the exact mechanism linking these conditions is unclear. Interestingly, oxytocin (Oxt) neurons, predominantly expressed in the hypothalamic paraventricular nucleus (PVN), play a crucial role in both obesity and anxiety. In this study, obesity can induce anxiety‐like behavior in mice, which can be ameliorated by the activation of PVN Oxt neurons. Conversely, inhibiting PVN Oxt neurons accelerate the progression of anxiety. Moreover, the family with sequence similarity 172, member A (Fam172a), an anxiety susceptibility gene, is highly expressed in the hypothalamic PVN Oxt neuron but reduce in the PVN Oxt neuron of mice in the high‐fat diet and acute restraint stress conditions. Significantly, overexpression of Fam172a in PVN Oxt neurons improve obesity‐anxiety‐like behavior in mice. In contrast, disruption of Fam172a in PVN Oxt neurons exacerbate obesity‐anxiety‐like behavior. Furthermore, this study demonstrates that Fam172a is involved in mRNA degradation in Oxt neurons by regulating the intranuclear transport of Argonaute 2, thereby influencing Oxt secretion and ultimately impacting obesity‐anxiety‐like behavior. These findings suggest that Fam172a serves as a key target of PVN Oxt neurons in the regulation of obesity‐induced anxiety.